Production and characterisation of gilthead sea bream (Sparus auratus) recombinant parathyroid hormone related protein - Anjos, Liliana (2014)
The production and puriWcation of gilthead sea bream recombinant parathyroid hormone related protein [sbPTHrP(1–125)] using an Escherichia coli system and one step puriWcation process with continuous elution gel electrophoresis is reported. The cDNA encoding sbPTHrP(1–125) was cloned into a prokaryotic expression vector pET-11a. The recombinant plasmid was used to transfect E. coli BL21(DE3) pLysS and sbPTHrP(1–125) synthesis was induced by addition of 1mM isopropyl- -D-thiogalactopyranoside. The rapid one step isolation method gave pure sbPTHrP(1–125) as judged by SDS–PAGE and yielded up to 40mg/L of culture medium (3.3mg protein/g of bacteria). The bioactivity of recombinant sbPTHrP(1–125) assessed using an in vitro scale bioassay was found to be equipotent to PTHrP(1–34) in stimulating cAMP accumulation. Assessment of the immunological reactivity of the isolated protein by Western blot revealed it cross-reacts with antisera speciWc for the N-terminal and C-terminal region of PTHrP. In a radioimmunoassay speciWc for piscine N-terminal (1–34 aa) PTHrP, the recombinant sbPTHrP(1–125) was equipotent with PTHrP(1–34) in displacing labelled 125I-PTHrP(1–36) PTHrP from the antisera. The availability of recombinant sbPTHrP will allow the development of region speciWc assays and studies aimed at deWning post-secretory processing of this protein and its biological activity in fish.